TroubleSpot.Painting. - Jarton, Cyril; Peeters, Wim; Reust, Hans Rudolf; Geyskens, Vincent; MUHKA, Antwerpen; NICC, Antwerpen (Antwerpen : NICC, MUHKA, 1999)
Andriesse, Jan ; Arocha, Carla ; Baldessari, John ; Beckett, Samuel ; Claerbout, David ; De Keyser, Raoul ; Dumas, Marlene ; Ghekiere, Joris ; Klein, Yves ; Ofili, Chris ; et al.
Troublespot.Painting, NICC en MUHKA, Antwerpen, 8 mei tot 22 augustus 1999
kunstcatalogus